The Photoshop CS book for digital photographers - Kelby, Scott (Voices that matter., 2003)
This update is so important, because if there was ever a version of Photoshop that was aimed at digital photographers, Photoshop CS is it, and "The Photoshop CS Book for Digital Photographers" by Scott Kelby (Editor of Photoshop User magazine) once again breaks new ground by doing something for digital photographers that's never been done before--it cuts through the bull and shows you exactly "how to do it." It's not a bunch of theory; it doesn't challenge you to come up with your own settings or figure it out on your own. Instead, it shows you step by step the exact techniques used by today's cutting-edge digital photographers and retouchers, and it does something that virtually no other Photoshop book has ever done -- it tells you, flat-out, which settings to use, when to use them, and why. If you're looking for one of those "tell-me-everything-about-the-Unsharp-Mask-filter" books, this isn't it. You can grab any other Photoshop book on the shelf, because they all do that. Instead, this book gives you the inside tips and tricks of the trade that today's leading pros use to correct, edit, sharpen, retouch, and present their photos to some of the most demanding clients on the planet. You'll be absolutely amazed at how easy and effective they are--once you know the secrets. LEARN HOW THE PROS DO IT Each year Scott trains thousands of professional photographers how to use Photoshop, and almost without exception they have the same questions and the same problems -- that's exactly what Scott covers in this book. You'll learn: The secrets of how the pros retouch portraits How to color correct any photo without breaking a sweat (you'll be amazed at how they do it!) How to unlock the power of Photoshop CS' new features for digital photo pros Amazing digital body-sculpting techniques How the pros use CS' File Browser (it's much more powerful than you think) Tricks that can send your productivity through the roof The sharpening techniques the pros really use (there's an entire chapter just on this!) How to deal with common digital camera image problems Removing noise, avoiding halos, and protecting your images How to use Match Color, The Color Replacement Tool, and other amazing CS tools. Masking techniques for photographers The most-requested photographic special effects and much more! Photoshop CS is THE tool for digital photographers, and this book show you exactly how to put it's power to work for you today.